Implementasi Kebijakan Merdeka Belajar-Kampus Merdeka pada Perguruan Tinggi di Kalimantan Tengah: The Policy Implementation of the Merdeka Belajar-Kampus Merdeka Program at Universities in Central Kalimantan - Sahay, Marvy Ferdian Agusta; Syamsuri, Syamsuri; Ulfah, Sri Mujiarti; Jaya, Imanuel; Ratnasari, Puput; Gaffar, Ummu Habibah; Angela, Vivi Friskila; Bertho, Edward Melio (Anterior Jurnal, 2024)
One of today's common problems is the high unemployment rate, dominated by university graduates. The Independent Learning Independent Campus (MBKM) program emerges as a policy response to answering this problem by attempting to make a link and match between learning in higher education and the needs in the world of work. This study aims to investigate how the MBKM policy has been implemented in several universities in Central Kalimantan. The study was conducted using a qualitative method by taking loci in three large universities in Central Kalimantan. The results found that several problems hinder the implementation of the MBKM Program.